Two lives of Anton Facuna - Daneková, Adriana (Romano džaniben, 2022)
Anton Facuna was born in 1920 in Horné Jaseno (today Turčianske Jaseno). When he was nineteen, Second World War broke out. Even though Jews and Roma were banned from the Slovak armed forces, A. Facuna took his military oath on 28 October 1941, in Ružomberok. In May 1944, he was sent to the Slovak technical division in Italy and assigned to the 102 infantry regiment. Soon, however, he defected to join the Czechoslovak foreign army. He became member of the DAY team of the DAWES mission organized by the American Office of Strategic Services, as part of its operations in central Slovakia. The second significant part of his life is associated with the effort to emancipate the life of the Roma in Slovakia. He was one of the founding members of the Union of Gypsies/Roma in Slovakia, its chairman and the director of its economic division, the Buťiker. Due to disagreements in the Union, he was ousted from the position of the Union's chairman and resigned from the position of director of Buťiker. He continued to work on various materials related to the history, language and emancipation of the Roma. He died in 1980 in Bratislava.
Keywords: Roma; Anton Facuna; World War II; DAY mission; Union of Gypsies/Roma in Slovakia